The HIV glycan shield as a target for broadly neutralizing antibodies. (23rd October 2015) - Doores, Katie J.
Abstract : The HIV envelope glycoprotein (Env) is the sole target for HIV broadly neutralizing antibodies (bnAbs). HIV Env is one of the most heavily glycosylated proteins known, with approximately half of its mass consisting of host‐derived N‐linked glycans. The high density of glycans creates a shield that impedes antibody recognition but, critically, some of the most potent and broadly active bnAbs have evolved to recognize epitopes formed by these glycans. Although the virus hijacks the host protein synthesis and glycosylation machinery to generate glycosylated HIV Env, studies have shown that HIV Env glycosylation diverges from that typically observed on host‐derived glycoproteins. In particular, the high density of glycans leads to a nonself motif of underprocessed oligomannose‐type glycans that forms the target of some of the most broad and potent HIV bnAbs. This review discusses the changing perception of the HIV glycan shield, and summarizes the protein‐directed and cell‐directed factors controlling HIV Env glycosylation that impact on HIV bnAb recognition and HIV vaccine design strategies. Abstract : The HIV envelope glycoprotein, Env, is extensively decorated with host‐derived N ‐linked glycans. These glycans not only shield conserved protein regions from antibody recognition but, critically, act as epitopes for some of the most broad and potent neutralizing antibodies. This review summarizes the protein‐directed and cell‐directed factors controlling HIV Env glycosylation that impact anti‐HIV antibody recognition and HIV vaccine design strategies.